Herpes zoster granulomatous dermatitis in metastatic lung cancer treated with nivolumab: A case report. Issue 5 (5th March 2020) - Gozzi, Elisa; Rossi, Luigi; Angelini, Francesco; Leoni, Valentina; Trenta, Patrizia; Cimino, Giuseppe; Tomao, Silverio
Abstract: Granulomatous dermatitis (GD) is the most common among a variety of skin reactions that may occur in the varicella‐zoster virus (VZV) reactivation area. It is thought that the formation of granulomas may be the result of a delayed hypersensitivity reaction to viral envelope glycoproteins. Immune checkpoint inhibitors (ICIs), such as nivolumab stimulate T cells and promote hypersensitivity reactions, leading to the formation of granulomas in VZV wrapping proteins, thus triggering VZV‐GD. Few cases of the use of ICIs in patients diagnosed with VZV‐GD have been reported in the literature. Here, we report the clinical case of a patient with metastatic lung cancer which was treated with nivolumab who subsequently developed VZV‐GD. Accurate clinical diagnosis and prompt treatment with antiviral agents have resulted in a complete resolution of the clinical picture. Key points: Significant findings: Treatment with ICIs may result in VZV reactivation. Accurate differential diagnosis and early treatment led to the resolution of VZV‐GD. What this study adds: Few cases of ICI and VZV reactivation have been reported in the literature. Full and timely resolution of VZV‐GD allowed the continuation of ICI treatment.